(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Phytochemical studies on the woods of Vatica pauciflora and Vatica lowii have been conducted. The woods of V. pauciflora were extracted with methanol by using Soxhlet apparatus while the woods of V. lowii were extracted with acetone at room temperature. The methanolic extract of V. pauciflora was semi-purified by using vacuum liquid chromatography (VLC) and further purified by high performance liquid chromatography (HPLC) to obtain a pure compound (1). The same technique of semi-purification has been employed on V. lowii acetone extract which was further purified by radial chromatography to give a pure compound (2). Based on the UV, IR, NMR and mass spectral data, the isolated compounds were characterized as (-)-cis-resveratrol-10-C-b-D-glucopyranoside and (-)-piceid respectively.